1996
DOI: 10.1063/1.362136
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of nanosized wires

Abstract: Assemblies of ferromagnetic cylinders made of Ni with diameters ranging from 35 to 250 nm were produced by electrodeposition in nanoporous membranes. The large coercive fields of Ni nanowires at low temperature could be accounted for by the curling mode of magnetization reversal, taking into account the distributions of wire diameters and orientations. The coercive field of the nanowires of the smaller diameter range decreased from 1500 Oe at 20 K to 200 Oe at 300 K nearly linearly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 17 publications
1
57
1
Order By: Relevance
“…Co/Cu multilayers are grown by electrodeposition in commercial ion-track-etched polycarbonate membranes of 6 mm in thickness [9,10]. The electroplating is performed in the conventional tree electrodes method.…”
Section: Techniquementioning
confidence: 99%
“…Co/Cu multilayers are grown by electrodeposition in commercial ion-track-etched polycarbonate membranes of 6 mm in thickness [9,10]. The electroplating is performed in the conventional tree electrodes method.…”
Section: Techniquementioning
confidence: 99%
“…Among them, Cobased anisotropic nanomaterials are attracting a great part of scientific interest mainly for their possible applications as nanomagnets in (nano)medicine [10] and recording media [11], and as building blocks in high energy nanostructured bulk magnets [12]. All these studies showed that depending on the elaboration process, the nanowires can present very different size, shape, morphology and crystal symmetry as well as very different as-grown spacing between the nano-objects [7,[14][15][16][17][18][19][20][21][22]. Thus, altogether, those parameters give rise to a wide ensemble of magnetic behaviors that are far from being fully controlled.…”
Section: Introductionmentioning
confidence: 99%
“…It was presented in Refs. [7,8] that the uniaxial anisotropy may be related to the presence of the polycarbonate membrane and to the chemical bonding existing between polycarbonate matrix and Ni wires. The thermal stresses induced in the nanowires due to the different thermal expansion constants of the Ni and polycarbonate result in magnetostrictive effects which should be taken into account.…”
Section: Resultsmentioning
confidence: 99%